The Impact of C-Peptide and Diabetes Mellitus on Coronary Ectasia and Effect of Coronary Ectasia and C-Peptide on Long-Term Outcomes: A Retrospective Cohort Study - Kenan Toprak; Mustafa Kaplangoray; Ali Palice (International Journal of Clinical Practice)
Background. Coronary artery ectasia (CAE) is an entity frequently associated with atherosclerotic coronary artery disease (CAD) in clinical practice. Although it has common risk factors with atherosclerotic CAD in its development, the pathophysiology of CAE is not fully known and it is not seen in every CAD suggesting that different determinants may play a pivotal role in the development of CAD. This study aimed to reveal the impact of C-peptide and diabetes mellitus (DM) on CAE and the effect of C-peptide and coronary ectasia on long-term outcomes in patients who underwent coronary angiography. Methods. A total of 6611 patients who underwent coronary angiography were followed up retrospectively, and their major adverse cardiovascular event (MACE) status of an average of sixty months was recorded. According to their angiographic features, the patients were divided into two groups those with and without CAE. MACE development was accepted as the primary endpoint. Results. A total of 552 patients had CAE and MACE developed in 573 patients. Patients with CAE and higher C-peptide levels (Q4 + Q3) showed higher rates of MACE as compared to those without CAE and lower C-peptide levels (Q1 + Q2) (20.8% vs 7.6%; 70.1% vs 29.1%; p<0.001, for both of them). In multivariate regression analysis, high C-peptide levels were determined as an independent risk factor for CAE (OR 2.417; 95% CI 2.212–2.641; p<0.001). The Kaplan–Meier cumulative survival curves showed that the risks for MACE increased as the C-peptide levels increased. The Cox regression analysis for 5-years MACE related to the plasma C-peptide levels and presence of CAE, C-peptide, and CAE were found to be independent predictors of MACE (HR = 1.255, 95% CI: 1.164–1.336, p<0.001 and HR = 1.012, 95% CI: 1.002–1.023, p=0.026, respectively). Conclusion. Our study revealed that a high C-peptide level is an independent risk factor for CAE and that CAE and C-peptide are independent predictors for the development of MACE.